Studi Karakteristik Marshall Pada Campuran Aspal Dengan Penambahan Limbah Botol Plastik - Suhardi, Suhardi; Pratomo, Priyo; Ali, Hadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
This experiment aims to investigate the Marshall characteristics due to the variation addition ofPET (Polyethylene Terephthalate) at mixtures AC-BC (Asphalt Concrete-Binder Course) finelygraded with reference to the specification of Bina Marga 2010.From the result of aalysis has obtained the values of Marshall parameters, the value of the 1 stobject groups test and 2nd object groups test, for the parameters marshall meets the specificationsalready determined by the Bina Marga 2010 on the asphalt level range 6.38% up 6.5%, and theoptimum bitumen content value has been obtained is 6.44%.This research proves that with the addition of variations of PET (Polyethylene Terephthalate) in amixture of AC-BC (Asphalt Concrete-Binder Course) was affected to the Marshall characteristics,as high as the levels of addition PET (Polyethylene Terephthalate) so the value of stability willincrease but the percentage of the value of void content in the mix will be higher.Keywords: AC-BC(Asphalt Concrete-Binder Course), Marshall, PET(Polyethylene Terephthalate)